2019
DOI: 10.1186/s12888-019-2011-0
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of psychiatric inpatients in China: clinical and institutional correlates in a national sample

Abstract: BackgroundSurveying patients’ satisfaction is essential to improve patient-centered care, however, studies on satisfaction and their correlates among psychiatric inpatients are rare in China. This study aimed to measure satisfaction levels of psychiatric inpatients in a national sample and to examine individual and institutional correlates.MethodsAs part of the National Survey for the Evaluation of Psychiatric Hospital Performance, psychiatric inpatients from 32 tertiary psychiatric hospitals in 29 Chinese pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 38 publications
2
27
0
5
Order By: Relevance
“…We found that the provision of psychological treatment significantly contributed to family satisfaction, which is consistent with a previous report [23]. As patients and their family members are treated as customers [40, 41], and psychological treatment often focuses on listening and conflict resolution, it is not hard to understand why the number of psychological treatments for patients is significantly associated with higher satisfaction levels in both patients [23] and their families.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that the provision of psychological treatment significantly contributed to family satisfaction, which is consistent with a previous report [23]. As patients and their family members are treated as customers [40, 41], and psychological treatment often focuses on listening and conflict resolution, it is not hard to understand why the number of psychological treatments for patients is significantly associated with higher satisfaction levels in both patients [23] and their families.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with the satisfaction level of the inpatients [23], family members had a significantly higher total satisfaction score, and higher scores for the hospitalization cost dimension and doctor-patient/family communication dimension. The mean score of the family total satisfaction score was 23.46 in families vs. 23.35 in inpatients ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, understanding the state of patient satisfaction and what patients are most concerned about from a national perspective is necessary. However, little research has been conducted to evaluate the quality of healthcare institutions with respect to the patients, and most of these studies focused only on some particular regions [14,15] or particular diseases [16].…”
Section: Introductionmentioning
confidence: 99%